Inhibitory effects of curcumin on passive cutaneous anaphylactoid response and compound 48/80-induced mast cell activation - Choi, Yun-Ho; Yan, Guang-Hai; Chai, Ok Hee; Song, Chang Ho (Anatomy & cell biology, 2010)
Mast cells participate in allergies and inflammation by secreting a variety of pro-inflammatory mediators. Curcumin, the active component of turmeric, is a polyphenolic phytochemical with anti-tumor, anti-inflammatory, anti-oxidative, and anti-allergic properties. The effects of curcumin on compound 48/80-induced mast cell activation and passive cutaneous anaphylactoid reactions are unknown. In this report, we investigated the influences of curcumin on the passive cutaneous anaphylactoid response in vivo and compound 48/80-induced mast cell activation in vitro. The mechanism of action was examined by calcium uptake measurements and cAMP assays in mast cells. Curcumin significantly attenuated the mast cell-mediated passive cutaneous anaphylactoid reaction in an animal model. In agreement with this in vivo activity, curcumin suppressed compound 48/80-induced rat peritoneal mast cell (RPMC) degranulation and histamine release from RPMCs. Moreover, compound 48/80-elicited calcium uptake into RPMCs was reduced in a dose-dependent manner by curcumin. Furthermore, curcumin increased the level of intracellular cAMP and significantly inhibited the compound 48/80-induced reduction of cAMP in RPMCs. These results corroborate the finding that curcumin may have anti-allergic activity.